SOSIALISASI HUKUM KEPADA PELAJAR DAN MASYARAKAT DESA TAMAN JAYA - SUKABUMI - Mona Hana Pertiwi; Wahyu Anugrah Zebua; Junjun Junaedi; Sudin Saepudin; Aldoko Edi Grahito (Jurnal Abdi Nusa, 2023)
Tamanjaya Village is one of the villages in the Ciemas sub-district which originated from the expansion of Mekarjaya Village, which was formerly a Cirameng hamlet, part of Mekarjaya Village, Ciemas District, which consists of 4 hamlets, 10 RW and 44 RT. One of the problems in the village is the lack of legal awareness regarding the Urgency of Cyber Law's Interests in Interacting on Social Media for students and the community in the village, so that people do not know that crimes on social media can be reported and already have their own laws, so that we provide socialization of this law in village halls that are attended by the community so that in the future if a crime or fraud occurs, the community can report it to the authorities, increase community legal awareness, and knowledge for the Tamanjaya village community. Not only to the community, but we also do this outreach to students there. Because most of the social media users are young people and they will also be the successors of Tamanjaya Village. The method used in this legal socialization for SMPN 1 Ciemas is a site survey and licensing, preparation of socialization events, preparation of material to be delivered, and finally the socialization activity is carried out. , make and distribute invitation letters to village officials and community leaders in Tamanjaya Village, prepare presenters and materials to be delivered and socialization activities are carried out in Gor, Tamanjaya village. This activity still needs to be developed and improved because the law is not only about Cyber Law, public awareness of other laws is still lacking. Maybe this socialization can open the eyes of the public to the laws that exist in Indonesia